Mathematical modelling and numerical simulation of induction heating processes - Rappaz, Jacques; Świerkosz, Marek (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with numerical simulation of induction heating for tridimensional time-varying axisymmetric geometries. A mathematical model is presented together with the numerical scheme used to solve it. The whole is illustrated by results of sample computations.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka